2019
DOI: 10.1111/ajt.15547
|View full text |Cite
|
Sign up to set email alerts
|

Use of ex vivo normothermic machine perfusion after normothermic regional perfusion to salvage a poorly perfused DCD kidney

Abstract: Abbreviations: CIT, cold ischemia time; DCD, donation after circulatory death; NMP, normothermic machine perfusion; NRP, normothermic regional perfusion; RBF, renal blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In each of the cases, NMP was used to salvage the kidneys after they were inadequately flushed during retrieval. 127 , 128 In 1 case, the kidney was retrieved after NRP. In both cases, the kidneys performed well during NMP and were transplanted successfully.…”
Section: Kidney Preservation Techniquesmentioning
confidence: 99%
“…In each of the cases, NMP was used to salvage the kidneys after they were inadequately flushed during retrieval. 127 , 128 In 1 case, the kidney was retrieved after NRP. In both cases, the kidneys performed well during NMP and were transplanted successfully.…”
Section: Kidney Preservation Techniquesmentioning
confidence: 99%
“…In addition, several groups are exploring the use of normothermic machine perfusion to evaluate and optimize kidneys preā€implantation 25 . Kidneys with subā€optimal perfusion have been successfully evaluated and transplanted after a period of machine perfusion 17,26 . Our data may help identify kidneys that could benefit from such ā€œrescue therapy.ā€ This would particularly be valuable for grade 2ā€“4 kidneys, where there is doubt regarding their viability.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our group reported that the use of ex vivo NMP after normothermic regional perfusion improved a poorly perfused DCD kidney that was then transplanted into a suitable recipient. The recipient had slow early graft function, but did not require dialysis posttransplant, and was discharged six days later with an SCr of 160 Ī¼mol/L (1.8 mg/dL) at two months posttransplant [ 36 ]. Therefore, discarded DCD donor kidneys, at least some of them, could be salvaged by NMP.…”
Section: Discussionmentioning
confidence: 99%